A Brain Computer Interface to Control Home Appliances for Epilepsy Patients - Mariappan, R.; Aarthi, M. G.; Kalaiselvi, P.; Kanimozhi, M. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
A brain computer interface (BCI) is a new communication channel between the human brain and the smart home appliances. EEG based non-invasive BCI with frequency filter algorithm was connected with a Virtual Reality system in order to control home appliances by using GUI platform. It offers an alternative to natural communication and control with human brain assumption and the ON OFF condition of home appliance is based on the muscle movement with interrupts.